Identification of novel pathogenic variants and features in patients with pseudohypoparathyroidism and acrodysostosis, subtypes of the newly classified inactivating PTH/PTHrP signaling disorders. Issue 7 (1st May 2019) - Truelove, Adam; Mulay, Akhilesh; Prapa, Matina; Casey, Ruth T.; Adler, Amanda I.; Offiah, Amaka C.; Poole, Kenneth E. S.; Trotman, Jamie; Al Hasso, Namir; Park, Soo‐Mi
Abstract: Albright hereditary osteodystrophy (AHO) is a complex disorder defined by the presence of a short adult stature relative to the height of an unaffected parent and brachydactyly type E, as well as a stocky build, round face, and ectopic calcifications. AHO and pseudohypoparathyroidism (PHP) have been used interchangeably in the past. The term PHP describes end‐organ resistance to parathyroid hormone (PTH), occurring with or without the physical features of AHO. Conversely, pseudopseudohypoparathyroidism (PPHP) describes individuals with AHO features in the absence of PTH resistance. PHP and PPHP are etiologically linked and caused by genetic and/or epigenetic alterations in the guanine nucleotide‐binding protein alpha‐stimulating (Gs α) locus ( GNAS ) in chromosome 20q13. Another less‐recognized group of skeletal dysplasias, termed acrodysostosis, partially overlap with skeletal, endocrine, and neurodevelopmental features of AHO/PHP and can be overlooked in clinical practice, causing confusion in the literature. Acrodysostosis is caused by defects in two genes, PRKAR1A and PDE4D, both encoding important components of the Gs α‐cyclic adenosine monophosphate‐protein kinase A signaling pathway. We describe the clinical course and genotype of two adult patients with overlapping AHO features who harbored novel pathogenic variants in GNAS (c.2273C > G, p.Pro758Arg, NM_080425.2) and PRKAR1A (c.803C > T, p.Ala268Val, NM_002734.4), respectively. We highlight the value of expert radiological opinion and molecular testing in establishing correct diagnoses and discuss phenotypic features of our patients, including the first description of subcutaneous ossification and spina bifida occulta in PRKAR1A ‐related acrodysostosis, in the context of the novel inactivating PTH/PTH related peptide signaling disorder classification system.